2016
DOI: 10.1002/adem.201600295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Porosity and Milling Induced Defects on the Thermoelectric Properties of p‐Type Bi2Te3‐Based Bulks

Abstract: The p-type (Bi,Sb) 2 Te 3 bulks are prepared from ball-milling powders by resistance pressure sintering method and their thermoelectric properties are investigated as a function of ball milling time. Prolonging milling time would introduce more anti-site defects, interaction of vacancies and antisite defect, grain-boundaries and interface defects, leading to lower carrier concentration and mobility. The peak value of ZT ¼ 1.0 is achieved at 300 K for the 5 h sample. When the testing temperature is over 323 K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In contrast to Sb 2 Te 3 -based and Bi 2 Te 3 -based materials 12 , 23 25 , 27 – 31 , whose S 2 σ values increase or decrease as the temperature increases, the temperature stability of S 2 σ of the hierarchical Bi 1.5 Sb 0.5 Te 3 nanopillar array with a tilt angle of 45° are useful in practical use. It is clearly demonstrated that the hierarchical Bi 1.5 Sb 0.5 Te 3 nanopillar array with a tilt angle of 45° shows a largely enhanced power factor compared with the hierarchical nanopillar array with a tilt angle of 60° or 90° and previous results 29 32 . There is no doubt that the tilt architecture significantly aids in achieving high TE properties, especially for the hierarchical nanopillar array with a tilt angle of 45°.…”
Section: Resultssupporting
confidence: 50%
“…In contrast to Sb 2 Te 3 -based and Bi 2 Te 3 -based materials 12 , 23 25 , 27 – 31 , whose S 2 σ values increase or decrease as the temperature increases, the temperature stability of S 2 σ of the hierarchical Bi 1.5 Sb 0.5 Te 3 nanopillar array with a tilt angle of 45° are useful in practical use. It is clearly demonstrated that the hierarchical Bi 1.5 Sb 0.5 Te 3 nanopillar array with a tilt angle of 45° shows a largely enhanced power factor compared with the hierarchical nanopillar array with a tilt angle of 60° or 90° and previous results 29 32 . There is no doubt that the tilt architecture significantly aids in achieving high TE properties, especially for the hierarchical nanopillar array with a tilt angle of 45°.…”
Section: Resultssupporting
confidence: 50%
“…As the porosity increases, the carrier concentration n of these samples decreases from 4.30×10 19 to 1.84×10 18 cm −3 . Similar results were also obtained in other porous TE material . It needs to be mentioned here some indirect effects rather than just the porosity could affect the carrier concentration of the present porous CdO samples.…”
Section: Resultssupporting
confidence: 87%
“…It shows that the ZT values increase with the porosities in the samples B, C, and C′. However, when the porosity increases to ∼11.5% in sample D, both the carrier mobility and κ l decrease dramatically, which could result from the pore boundary scattering effect and the substantial decrease of effective thickness of the cross section, finally leading to a serious deterioration of the ZT value compared with other samples …”
Section: Results and Discussionmentioning
confidence: 95%
“…However, when the porosity increases to ∼11.5% in sample D, both the carrier mobility and κ l decrease dramatically, which could result from the pore boundary scattering effect and the substantial decrease of effective thickness of the cross section, finally leading to a serious deterioration of the ZT value compared with other samples. 55 Benefiting from the nanoporous structure, a high ZT value of ∼0.67 at room temperature is achieved in sample C′, which is enhanced by ∼60% compared with the dense sample A and could be further improved by optimizing the carrier concentration. 10 It suggests that tuning the porous structure with rational pore characters can scatter phonons with a wide spectrum of wavelengths and significantly reduce κ l .…”
Section: Methodsmentioning
confidence: 98%